Combined application of chemical and organic fertilizers enhances soil organic carbon sequestration and crop productivity by improving carbon stability and management index in a rice–rice cropping system - Hu Xu; Adnan Mustafa; Qudsia Saeed; Guiying Jiang; Nan Sun; Kailou Liu; Jiri Kucerik; Xueyun Yang; Minggang Xu (Chemical and Biological Technologies in Agriculture)
Abstract Soil organic carbon (OC) sequestration in farmlands can be improved through fertilizer applications, particularly with the addition of organic amendments. However, our knowledge of the effects of long-term different fertilization on OC chemical stability and carbon management index (CMI), as well as their response to crop productivity remains limited in rice–rice cropping system. The objectives of this study were to investigate the effects of fertilization on various OC sequestration indicators in bulk soil and chemical fractions, and establish their relationships with crop productivity. The treatments selected in the present study were those which had undergone long-term fertilization under double-rice cropping including: (1) no fertilization (CK); (2) combined application of chemical nitrogen, phosphorous, and potassium fertilizers (NPK); (3) the doubled rate of NPK treatment (2NPK); and (4) NPK treatment plus organic fertilizers (NPKM). After 29 years of fertilization, we observed that NPKM resulted in the highest OC stocks (11.47 and 26.15 Mg ha−1, respectively) and distribution ratios (24 and 54%, respectively) in the less-labile fraction and passive pool. Conversely, it showed the lowest OC values in the labile fraction and active pool compared to CK, NPK, and 2NPK treatments. Additionally, NPKM significantly (P < 0.05) increased CMI (by 47 and 33%) over CK and NPK treatments, which suggests that soil receiving NPKM was better managed. Apart from maintaining higher crop yields and increasing OC input, NPKM also tremendously enhanced OC sequestration as indicated by the highest soil OC stock (48.80 Mg ha−1) and OC sequestration rate (CSR, 0.37 Mg ha−1 yr−1). There was an increasing trend of CSR and passive OC pool, but a decreasing trend of carbon sequestration efficiency with increasing OC input, which may be associated with OC saturation behavior of soil. Furthermore, crop yield showed significant positive linear correlations with passive OC pool and CMI. In summary, long-term combined application of chemical and organic fertilizers enhanced OC sequestration and crop productivity by improving passive OC pool and CMI, which contributed to realize agricultural sustainability in double-cropping rice regions. Graphical Abstract